THE AUTHORITY OF THE SUB-DISTRICT HEAD IN EVALUATING DRAFT REGULATION OF THE VILLAGE REGARDING VILLAGE BUDGET IN CENTRAL BENGKULU BASED ON THE REGENT’S REGULATION OF CENTRAL BENGKULU NUMBER 34 OF 2018 REGARDING THE AUTHORITY DELEGATION OF THE REGENT TO THE SUB-DISTRICT HEAD IN EVALUATING DRAFT REGULATION OF THE VILLAGE REGARDING VILLAGE BUDGET AND DRAFT REGULATION OF THE VILLAGE ABOUT VILLAGE BUDGET AMENDMENT - Neny Zarniawati; Elektison Somi; Amancik Amancik (Bengkoelen Justice : Jurnal Ilmu Hukum, 2020)
The researcher will discuss the Sub-Districts Head authority in evaluating Draft Regulation of the Village regarding Village Budget (APBDes) in Central Bengkulu Regency based on the Regent’s Regulation of Central Bengkulu Number 34 of 2018 regarding the Authority Delegation of the Regent to the Sub-District Head in evaluating Draft Regulation of the Village regarding Village Budget and Draft Regulation of the Village about Village Budget Amendment (p-APBDes). The purpose of this research was to find out and to analyze the authority of the Sub-District Head in terms of evaluating the Draft Regulation of the Village regarding APBDes in Central Bengkulu Regency based on the Regent’s Regulation of Central Bengkulu Number 34 of 2018 regarding the Authority Delegation of the Regent to the SubDistrict Head in evaluating Draft Regulation of the Village Regarding APBDes and Draft Regulation of the Village about p-APBDes. This research was normative legal research. Data sources used were primary and secondary data sources. In collecting the data, the researcher used the methods of library studies and field studies. After the research was conducted, it canbe concluded that the authority of the Sub-District Head in evaluating the Draft Regulation of the Village regarding APBDes and P-APBDes in Central Bengkulu Regency was carried out based on the regulation mandate that stipulated in Law No. 6 of 2014 about Village, Law No. 23 of 2014 about Local Government, Government Regulations No. 43 of 2014 about Regulations for Implementing Village Laws, Government Regulations No. 17 of 2018 about sub-districts, Regulation of Minister of Home Affairs No. 20 of 2018 about Village FinancialManagement and Regent’s Regulation of Central Bengkulu number 34 of 2018 regarding the Authority Delegation of the Regent to the Sub-District Head in evaluating Draft Regulation of the Village Regarding APBDes and Draft Regulation of the Village about p-APBDes.